GREEN ECONOMY AS A PILLAR OF SUSTAINABLE DEVELOPMENT: INTEGRATION OF PUBLIC AND PRIVATE POLICIES IN REDUCING CARBON EMISSIONS - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Green economy is a strategic approach in realising sustainable development oriented towards reducing carbon emissions, preserving the environment, and improving social welfare. This article discusses the importance of public and private policy integration in supporting the transition to a low-carbon economy. The government plays a role through regulation, incentives, and development of green infrastructure, while the private sector contributes through technological innovation, investment, and implementation of sustainable practices. Synergy between these two sectors is needed to increase the effectiveness of climate change mitigation, while creating new economic opportunities such as green jobs. With an integrated green economy approach, it is expected that sustainable development can be realised without compromising the ecological balance in the future.